Legal protection for copyright holders of commercialized remix song cover version - Gorda, AAA. Ngurah Sri Rahayu; Artami, Ida Ayu Ketut; Antari, Putu Eva Ditayani; Sudharma, Kadek Januarsa Adi; Vaisile Moisa, Robert (Faculty of Law, University of Muhammadiyah Malang, 2022)
Copyright is legal and registered work. a copyright holder has two exclusive rights: economic and moral rights. A song or music copyright is one of the copyrights in the realm of art. However, there have been several copyright infringements in the music industry recently, and the cover version of a song is one of many. Many performers cover songs without the consent of original composers. They also sell and buy the music, which has obviously taken away the creator's economic and moral rights. As a result, legal protection for composers is required to prevent future instances of copyright infringements of music. The objective of this study is to determine the legal protection afforded to copyright holders of the commercialized version of a cover song, as well as the purposeful conclusion of the case involving the marketed version of the covered song. This research employed a normative approach based on literature. This study's technical analysis employed descriptive - qualitative methods. Two types of legal protection for songwriters constitute preventative and repressive protection, where the former is achieved by registering works held by the Directorate General of Intellectual Property Rights and undertaking public awareness campaigns emphasizing the significance of copyright recognition. Meanwhile, repressive protection is sought by filing a civil complaint, and criminal charges to the District Court. There are two options to resolve copyright issues over songs: in court or outside court, where the litigation process involves filing a case to the district court, and the non-litigation process may require negotiation.